3C 390.3 - JET OR DISK - Nazarova, L. S.; Bochkarev, N. G.; Gaskell, C. M. (Одеські астрономічні публікації, 2007)
Analysis of the UV and optic spectra of the active galaxy 3C 390.3 shows that the observed line ratios for the broad components of lines: CIV/Lα, Lα/Hβ and Hα/Hβ can be accounted by two system of clouds. One corresponds to the region with an electron density 108-10 cm -3, located above an accretion disk - probably in jets. This region emits the high ionization lines Lα and CIV at the distance ≈ 40-60 days and low ionization lines Hβ and Hα at the distance ≈ 80 days. The other system corresponds to the zone which is probably part of an accretion disk and has a higher electron density 1012-13 cm-3.